A comparison of the perceptual-motor performance of seven-and eight-year-old learning-disabled and non-handicapped children - Mehrman, Dorothy (My University, 1983)
The purpose of this study was to determine if differences exist in performance among seven-and eight-year-old children classified as learningdisabled and non-handicapped on the Southern California Perceptual-Motor Tests (SC~T)an d four selected perceptual-motor tasks designed by the researcher. The SCmT consisted of eight subtests: (1 ) Position in Space, (2) Motor Accuracy-Revised, (3) Imitation of Postures, (4) Bilateral Motor Coordination, (5) Right-Left Discrimination, (6) Crossing Midline of Bodrr. (7) Standing Balance-Eyes Open, and (8) Standing Balance-Eyes Closed. The four selected perceptual-motor tasks included: (1) a Scooter Activity, (2) a Hopscotch Activity, (3) a Ball Activity, and (4) a Eeam Activity. The SCFMT was administered to 37 sub,jects, and the selected tasks to 31 subjects. The learning-disabled population was chosen first, with the non-handicapped population subsequently selected with an attempt made to correlate the ages, sex, and schools of the learning-disabled and nonhandicapped subjects. A two-way ANOVA was computed for the raw scores for each of the eight-subtests of the SCPNT, and a three-way ANOVA with repeated measures was computed for each of the four selected tasks, with two trials per task representing the repeated measures. Results of the statistical analyses revealed consistency in significant between group differences which favored the non-handicapped group in five of the eight SCPNT subtests, while for the tasks they were noted in only the Scooter Activity. Age by group interactions were noted on three of the SCWiT subtests, while none were noted for the selected tasks. The Ball Activity displayed significant between age difference which indicated better performance for the eight-year-old group, while none were evident for the SCPMT. Between trial differences indicating better performance on Trial 2 regardless of age or group were noted on three of the four tasks, while a trial by group interaction was noted on the Beam Activity.
Keywords: Children with disabilities - Education; Motor ability in children - Testing; Perceptual-motor learning